O ensino de geografia problematizado a partir das experiências vividas pelo estágio supervisionado no Colégio de Aplicação de Araguaína, Tocantins. - Rocha, Diêgo de Aguiar (Universidade Federal do Tocantins, 2023)
This paper discusses the importance of supervised internship for the formation process of teacher in Graduation in Geography of Federal University of Tocantins (FUT), Campus of Araguaína, TO, and also does an analysis about geography teaching in school, from the experiences lived through supervised internship in School of Application of Araguaína, TO. It had for objectives to understand, through the internship, the transition process between the university academic and the future role of teacher; to detail the physical, educational and pedagogical conditions that the school provides for the development of the internship; and to report the experiences lived during the supervised internship, showing the difficulties and the knowledge involved in the process of formation of geography teacher. For that, it was performed a bibliographic review in the specialized literature and also a rescue in memory about the experiences of internship. This study enabled a reflection about internship in the course of graduation of geography teacher and also about the teaching of geography. During the internship, difficulties were encountered as the indiscipline of the students, but also were acquired knowledge to deal such a situation. Yet, it’s realized a geography teaching focused on the use of concepts already defined in books, without a problematization of issues with reality. The internship allowed a moment of learning of school reality, contributing to academic education.